Biologia como polinização como ferramenta para delimitação de espécies - De Bastiani, Aline (2019)
The native flora preservation of a region is closely linked to the intrinsic knowledge of the organisms which compose it. The correct identification of plant species and the determination of their ecological and reproductive needs are fundamental elements to promote efficient conservation strategies. Studies related to plant taxonomy are often based only on morphological characters, which makes it difficult to accurately interpret the taxonomic position of many species. In this sense, the analysis of the reproductive systems and the biology of the pollination serve as a subsidy to clarify possibly wrong hypotheses. The recent discovery of the plant species Sinningia lutea has caused divergences in the scientific environment, with a tendency to incorporate it to the present Sinningia allagophylla, although they have very different structural characteristics. Thus, the present study aimed to determine if Sinningia lutea and Sinningia allagophylla should, in fact, be considered distinct taxonomic entities, based on analysis of the pollination biology and the reproductive system of both species. In order to define the pollinators of each species, observations were made in environments of natural occurrence of S. lutea and S. allagophylla, with support of videos and photographic records. In addition, we determined the volume and concentrations of nectar, the latter being an important factor in determining the pollinator. We also analyzed comparatively the morphological characteristics of both species, relating them to the corresponding pollinator. Also, we determine the reproductive system, which indicates the dependence or not of pollinators activity for the reproductive success of the species (self-compatibility). Our results indicate significant differences in morphological characters and nectar concentration between the two species. Sinningia lutea has yellowish-colored flowers and shorter and broader corollas, as well as much more concentrated nectar (bee pollination characteristics), while Sinningia allagophylla has reddish color and longer and narrower corollas, including much more diluted nectar (pollination characteristics by hummingbirds). In addition, our field observations confirmed the distinction of pollinators between species. Sinningia lutea is pollinated by Centris (Heterocentris)analis bees, while Sinningia allagophylla is pollinated by hummingbirds Chlorostilbon lucidus. Both species are self-supporting, but dependent on pollinators. Therefore, Sinningia lutea and Sinningia allagophylla are biologically separated and may be considered independent species. Our results highlight the importance of the study of ecological relations, such as the biology of pollination, associated to the evolutionary history of the plants to establish correct taxonomic relations and to promote appropriate methodologies for the maintenance of the species.